Prevalence of antibiotic‐resistant bacteria in freshwater fish farms. (19th December 2020) - Sherif, Ahmed H.; Gouda, Mofeed; Darwish, Shawky; Abdelmohsin, Asmail
Abstract: The emergence of antibiotic‐resistant bacteria (ARBs) has become a threat to the aquatic industry. Virulent bacterial spp. namely Aeromonas hydrophila, A. veronii, Pseudomonas fluorescens and P. aeruginosa that were isolated from Nile tilapia ( Oreochromis niloticus ) and grey mullet ( Mugil cephalus ) were collected from freshwater fish farms at three different sites, and their associated antibiotic‐resistant genes (ARBs) were further characterized. The ARGs for sulphonamide and tetracycline were the most prevalent ones. Out of 50 O. niloticus and 50 M. cephalus, A. hydrophila (16.5 ± 5.5 and 11 ± 1.0 respectively) and P. aeruginosa (16 ± 1.0 and 12.5 ± 2.5 respectively) had significantly higher infection rates. At site 3, O. niloticus and M. cephalus showed severe lesions in the hepatic tissues which had higher residues of iron (Fe, 1238.3–1250.0 µg/g) and zinc (Zn, 940.0–078.0 µg/g) compared with sites 1 and 2. The severity of hepatic tissue lesions was associated with bacterial infection and heavy metal residues, and also the presence of ARGs was associated with histopathological alterations of the hepatic tissues. It was concluded that ARGs (sulphonamide and tetracycline) could be developed in bacteria isolated from fish, which subjected to heavy metal pollution (Fe, Mn and Zn).